KEEFEKTIFAN MODEL EXPERIENTIAL LEARNING DAN QUANTUM TEACHING DALAM PEMBELAJARAN MENULIS PUISI BERTEMA KEPEDULIAN SOSIAL PADA SISWA KELAS VIII SMP (Jurusan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2018)
Abstrak Model pembelajaran merupakan sarana interaksi dalam kegiatan belajar mengajar sebagai salah satu pola instruksional. Penelitian ini bertujuan untuk (1) mendeskripsikan keefektifan model experiential learning dalam pembelajaran menulis puisi bertema kepedulian sosial pada siswa kelas VIII SMP Islam Sudirman Ambarawa; (2) mendeskripsikan keefektifan model quantum teaching dalam pembelajaran menulis puisi bertema kepedulian sosial pada siswa kelas VIII SMP Islam Sudirman Ambarawa; dan (3) menentukan model manakah yang lebih efektif digunakan dalam pembelajaran menulis puisi bertema kepedulian sosial pada siswa kelas VIII SMP Islam Sudirman Ambarawa. Hasil penelitian menunjukan rata-rata post-test kelas eksperimen model experiential learning sebesar 80,07, dan kelas eksperimen model quantum teaching sebesar 76,55. Dapat disimpulkan model experiential learning lebih efektif digunakan dalam pembelajaran menulis puisi bertema kepedulian sosial pada siswa kelas VIII SMP Islam Sudirman Ambarawa. Kata kunci: model experiential learning; model quantum teaching; teks puisi; kepedulian sosial. Abstract Learning model is an interaction facility in teaching and learning activities which is as one of instructional patterns. The objectives of the research are (1) to describe the effectiveness of experiential learning model in learning to write poetry themed social concern for Grade Eight students of Junior High School Islam Sudirman Ambarawa; (2) to describe the effectiveness of quantum teaching model in learning to write poetry themed social concern for Grade Eight students of Junior High School Islam Sudirman Ambarawa; and (3) to determine the more effective model to be implemented in learning to write poetry themed social concern for Grade Eight students of Junior High School Islam Sudirman Ambarawa. The results of the study show the average post-test experimental class of experiential learning model is 80,07, and experimental class of quantum teaching model is 76,55. It can be summarized experiential learning model is more effective to be implemented in learning to write poetry themed social concern for Grade Eight students of Junior High School Islam Sudirman Ambarawa. Keywords : experiential learning model, quantum teaching model, write poetry, social concern.